2022
DOI: 10.1177/00469580221098754
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cancer Knowledge, Attitudes, and Practices in Adolescents and Young Adults in Two Texas Rural Communities

Abstract: The Youth and Young Adults Cancer Knowledge Attitudes and Practices (C-KAP) exploratory study in 2 rural underserved areas in a border community. C-KAP is an interdisciplinary research pilot project led by university scholars in psychology and social work in partnership with community partners. The exploratory cross-sectional mix-method study recruited 141 (n =141) youth and young adults (ages 18-39). This study was informed on empirical research and a bilingual online questionnaire was field-tested, and data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Other sources of information, such as friends, teachers, newspapers, and magazines, had lower utilization rates in both countries. These findings are consistent with another study conducted in the United States, which found that young adults predominantly sought cancer information through social media platforms [ 24 ]. Understanding these preferences and identifying reliable and user-friendly information sources is essential for effectively reaching out to young adults.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Other sources of information, such as friends, teachers, newspapers, and magazines, had lower utilization rates in both countries. These findings are consistent with another study conducted in the United States, which found that young adults predominantly sought cancer information through social media platforms [ 24 ]. Understanding these preferences and identifying reliable and user-friendly information sources is essential for effectively reaching out to young adults.…”
Section: Discussionsupporting
confidence: 92%
“…This is expected since breast cancer and endometrial cancer are female-specific cancers. Some studies also showed that female students had higher recognition of HPV infection, uterine cancer, and breast cancer than male students [ 10 , 18 , 24 ]. Similarly, female medical students were found to have significantly better knowledge of HPV infection than male medical students [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Хоча інформацію про норми здоров'я легко отримати, пошук інформації щодо скринінгу та профілактики раку не є достатньо простим і зрозумілим. Тому превентивна освіта має сприяти поширенню відповідної інформації для охоплення широких верств населення країни [7].…”
Section: Bilyk Valentyna Hryhorivnaunclassified
“…Previous studies revealed that the KAP toward cancer in general was very variable among different populations [ [10] , [11] , [12] , [13] , [14] ], including cancer screening [ [14] , [15] , [16] ]. KAP studies were performed in patients with glioma [ 17 , 18 ] and healthcare providers [ 19 ], but no data are available regarding the KAP toward glioma of patients consulting for neurological symptoms in general.…”
Section: Introductionmentioning
confidence: 99%